HBsAg clearance and seroconversion case in a patient with HBeAg-negative chronic hepatitis B on pegylated interferon α-2a therapy - K. V. Zhdanov; D. A. Gusev; K. V. Kozlov; S. S. Zhabrov; A. V. Shekurov; A. V. Nagovitsyn; A. V. Mishin; E. V. Jakovleva (Журнал инфектологии, 2014)
Presented clinical case describes elimination followed by seroconversion HBsAg / HBsAb patient with HBeAg-negative chronic hepatitis B on antiviral therapy with pegylated interferon α2-a and achieving sustained virological response.